Development of an intelligent packaging material incorporating betacyanin from red beetroot extract into polyvinyl alcohol films - Moushumi Akter; Md. Nahidul Islam; Sabina Yasmin; Md. Sultan Mahomud (Future Foods)
This research aimed to develop an intelligent packaging material by incorporating betacyanin from red beetroot extract into polyvinyl alcohol (PVA) film. Betacyanin was extracted using three solvents (Distilled Water, Ethanol, and Methanol), and films were prepared. The methanolic extract had the highest betacyanin content (416.57µg/100g), while the distilled water extract had the lowest (310.22µg/100g). Incorporating betacyanin increased the film thickness, with methanol-extracted films (MEF) being the thickest (126.36µm). Light transmittance differed significantly, being highest in ethanol-extracted films (EEF) (4.32%) compared to control (3.65%) and MEF (3.82%). Water solubility was highest in the control sample (44.94%), and water vapor permeability was lowest in methanol-extracted films (14.25gmsPa-1 × 10-7), indicating better film quality. MEF had the lowest lightness (L*=31.71), while control films had the highest (L*=38.84). The a* value was lowest for control films (a*=1.97) and highest for methanol-extracted films (a*=6.08). EEF had the highest b* value (b*=6.58±0.95), and control films had the lowest (b*=4.01). All films exhibited low mechanical resistance with tensile strengths ranging from 2.84 to 3.16 MPa. Additionally, these films can detect pH changes, acting as promising colorimetric bioindicators. The study concludes that intelligent films made with methanol-extracted betacyanin are viable for developing pH-responsive packaging for the food industry.